KEANEKARAGAMAN KEPITING BIOLA DI KAWASAN MANGROVE KABUPATEN PURWOREJO JAWA TENGAH - Slamet Mardiyanto Rahayu; Wiryanto Wiryanto; Sunarto Sunarto (EnviroScienteae, 2017)
Mangrove is a unique ecosystem and has an important function ecologically, socio-economically, and education. The area of mangroves in Purworejo Regency is decreasing due to logging, settlement, ponds, and agriculture. Reduced mangrove stands will affect the existence of various fauna associated with it. Therefore it is done in August-September 2016 to know the diversity of the fiddler crabs in the mangrove area Purworejo District, Central Java. There are three stations, namely dense mangroves (Gedangan Village), medium mangroves (Jatikontal Village), and rare mangroves (Ngentak Village). From the research, there were 7 types of fiddler crab, Uca annulipes, U. crassipes, U. paradussumieri, U. rosea, U. tetragonon, U. vocans, and U. vomeris. The index of fiddler crab diversity in the mangrove area of Purworejo Regency, Central Java at station 1 (1.67) and station 2 (1.90) is moderate. The fiddler crab biodiversity index at station 3 (0.64) is low. Environmental conditions throughout the station are relatively good for mangrove life and fiddler crabs, ie temperature 26-30oC, pH 6-8, dissolved oxygen 3,5-6,6 mg / L, salinity 3-9 ppt, and sandy mud substrate. Vegetations of mangrove at station I are Rhizophora mucronata, Nypa fruticans, Sonneratia alba, and Hibiscus tiliaceus. Mangrove vegetation at station II is Sonneratia caseolaris, Rhizophora stylosa, N. fruticans, H. tiliaceus, and Morinda citrifolia. Vegetations of mangrove at station III are S. alba, S. caseolaris, N. fruticans, and R. mucronata. The density of mangrove vegetation is related to species abundance (density) of fiddler crabs.